PENGARUH LATIHAN RUBBER DAN BURBLE TERHADAP KEKUATAN DAN POWER OTOT LENGAN PADA PEMAIN BOLAVOLI - Suparto, Achmad (Jurnal Phederal Penjas, 2014)
Arm muscle strength and power are determinants in performing movements that require the achievement of success in performing a service effort and smash in volleyball games. Volleyball is a dynamic sport with a high level of intensity in performing movements and strategic techniques, either currently or survive when attacked. In this study to have the strength and the muscle?s power you need to have burble and rubber exercise.This research aims to analyze 1) the effect of rubber and burble training for arm muscle Strength and of volleyball player. 2) The effect of rubber and burble training for arm muscle power of volleyball player. The objects of this research are 30 junior volleyball players in Official Training Center Branch (Puslatcab), Sumenep.This research uses quantitative research by using quasi experiment method. The research used a matching only design. The One way Anova is used to analyze the data. The data is collected by using test. Push up test is used to measure arm muscle strength and Ball Medicine Throw is used to measure the power in the pretest and post test.Result: 1) On increasing the strength of the arm muscles of Anova test results stating F-count > F-tabel, or 37.227 > 3.35. it can be concluded that there are significant differences between the groups of rubber, the burble group and the control group. 2). On increasing muscle power arm of the Anova test results stating F-count > F-tabel, or 16.773 > 3.35. it can be concluded that there are significant differences between the groups of rubber, the burble group and the control group.Conclusion. Rubber exercise more effective at increasing muscle power rather than exercise arm burble and control. While exercise is more effective burble to increase muscle strength and rubber sleeves